The Effect of Digital Marketing Strategy, Price, and Product Quality on Sales Performance: Evidence from Rendang Cipuik GG SMEs in Indonesia - Jum’adil Dwi Zulstra (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
This research explores how digital marketing strategy, pricing, and product quality shape sales performance in Rendang Cipuik GG, a traditional small and medium-sized enterprise (SME) in Lima Puluh Kota Regency, Indonesia. Using a quantitative explanatory design, the study collected primary data from 100 consumers through a structured questionnaire and analyzed the responses using multiple regression and structural equation modeling with partial least squares (SEM-PLS). The findings show that both digital marketing strategy and product quality positively and significantly impact sales performance, while pricing did not have a significant individual effect on consumer purchasing decisions. However, when considered collectively, these three variables—digital marketing strategy, price, and product quality—jointly influence sales outcomes in a statistically significant way. These results highlight the importance of digital transformation for SMEs in heritage-based culinary industries, suggesting that modern consumers prioritize authenticity, consistent quality, and engaging digital marketing over price. The study contributes to SME marketing literature by integrating these three elements into a comprehensive framework for understanding sales performance, and provides practical guidance for SME owners and entrepreneurs, emphasizing that investment in digital platforms, product authenticity, and quality consistency are key strategies for maintaining competitiveness in the digital economy.